1996
DOI: 10.1063/1.116530
|View full text |Cite
|
Sign up to set email alerts
|

Hardness, elastic modulus, and structure of very hard carbon films produced by cathodic-arc deposition with substrate pulse biasing

Abstract: The hardness, elastic modulus, and structure of several amorphous carbon films on silicon prepared by cathodic-arc deposition with substrate pulse biasing have been examined using nanoindentation, energy loss spectroscopy ͑EELS͒, and cross-sectional transmission electron microscopy. EELS analysis shows that the highest sp 3 contents ͑85%͒ and densities ͑3.00 g/cm 3 ͒ are achieved at incident ion energies of around 120 eV. The hardness and elastic modulus of the films with the highest sp 3 contents are at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(103 citation statements)
references
References 15 publications
(25 reference statements)
5
96
1
1
Order By: Relevance
“…Dekempeneer et al 20 have presented a maximum value of about 14 GPa several years ago but currently they obtain hardnesses of 20 GPa for a-C:H deposited with an rf parallel-plate reactor. Robertson 4 and Pharr et al 24 report a maximum value of 17 GPa. All these hardnesses are obtained at a substrate bias of about 200 V per deposited carbon particle.…”
Section: Resultsmentioning
confidence: 99%
“…Dekempeneer et al 20 have presented a maximum value of about 14 GPa several years ago but currently they obtain hardnesses of 20 GPa for a-C:H deposited with an rf parallel-plate reactor. Robertson 4 and Pharr et al 24 report a maximum value of 17 GPa. All these hardnesses are obtained at a substrate bias of about 200 V per deposited carbon particle.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of DLC films prepared by energetic deposition strongly depend on ion energy [5,9,10,14]. Figure 2 shows the correlation between the film density and the carbon ion energy.…”
Section: Hard Coatingsmentioning
confidence: 99%
“…Typically, it has been observed that there is a correlation between the level of stresses and the sp 3 content in these films, which define their diamondlike properties [5,8,9]. Since the as-deposited DLC films with highest sp 3 content have very high levels of intrinsic stresses (as high as 10 GPa), thick films have tendency to delaminate from the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…For carbon, it is well known that films that are rich in sp 3 (diamond) bonds should be grown in a kinetic mode at low temperature (less than 200°C, preferably room temperature), with film-forming carbon atoms or ions having an energy of about 100 eV. This energy is optimized for subplantation film growth of diamond-like carbon [4][5][6][7][8][9][10]. If the energy is too low, say less than 20 eV, ions do not have the kinetic energy to penetrate the surface; if the energy is too high, thermal spikes and a general enhancement of the temperature will allow the carbon atoms of the film to move to configurations of smaller energy.…”
mentioning
confidence: 99%
“…[20,21] There are large variations even within each class of materials, depending on the method and parameters of deposition. Diamond-like carbon films can be synthesized by argon sputter deposition using a graphite target [12,22] [6,16,20,21]. Research over the last years has identified filtered cathodic arc deposition as one of the promising techniques for hard carbon films thinner than 5 nm [28,29].…”
mentioning
confidence: 99%